Analisis Dampak Digital Marketing Terhadap Keberhasilan Usaha UMKM di Era Digital - Zahra, Karina; Nur Adawiyah Harahap; Lubis, Pitri Aulia Usman (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
Digital marketing has become a key element in marketing strategies for micro, small, and medium enterprises (MSMEs) in the digital era. This study aims to analyze the impact of digital marketing on the success of MSME businesses, especially in increasing sales and brand awareness. The results of the study indicate that the implementation of digital marketing strategies including the use of social media, e-commerce, and search engine optimization (SEO) significantly contributes to increasing MSME revenue and competitiveness. In addition, digital marketing also makes it easier for MSMEs to reach wider consumers and increase interaction with customers. Thus, the adoption of appropriate digital marketing can be a determining factor for the success of MSMEs in an increasingly competitive market.